In-situ measurement of the meniscus at the entry and exit of grease and oil lubricated rolling bearing contacts - Gray, W. A.; Dwyer-Joyce, R. S. (Frontiers in Mechanical Engineering, 2022)
The lubricant inlet meniscus in a rolling element bearing acts as a reservoir that feeds the elastohydrodynamic contact, resulting in a sufficiently thick film to avoid wear. A shortening and/or thinning of the inlet meniscus towards the contact centre is an indicator of bearing starvation and impaired lubricant performance. This work introduces an ultrasonic method to measure meniscus dimensions. Using in-situ ultrasonic sensors on a full-scale cylindrical roller bearing test rig, we show that ultrasonic waves can cause oil films to resonate, and that the resonant frequency is directly related to the film thickness. Using a benchtop rig we validate the relationship between resonant frequency and film thickness. This allows for the measurement of meniscus thickness and length in-situ during bearing operation. Menisci were measured at both the inlet and outlet of rolling bearing line contacts while lubricated with different viscosity oils and grease. All lubricants used showed they could be monitored using this approach. The implication of this paper is that it is possible to measure a critically important lubrication mechanism during operation without major component modifications.